Hari Baba Movement (1931): The short-lived impact of the Hari Baba Movement on tribal communities (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Like several revivalist movements of the 19th and 20th centuries in the region of Chotanagpur in Bihar, Hari Baba movement led by Duka Ho in the Singhbhum district also attracted large number of followers and tried to reform the lives of his fellowmen cutting across the tribes. Like other movements in which we find the Gandhian influence, in this context the Hari Baba movement was not different from others. This movement ascended during the Civil Disobedience movement (1930-34) but went into oblivion with the arrest of the leader Duka Ho. Although the movement did not last very long but it had significant impact on the lives of tribals.